CREEP OF REINFORCED CONCRETE THIN-WALLED STRUCTURES TAKING INTO ACCOUNT REVERSE DEFORMATIONS: Array - Chuprynin, O.; Sereda, N.; Garbuz, A. (Municipal economy of cities. Series: «Economy science», 2020)
One of the main tasks, which is solved at the design stage of the reinforced concrete element, is the analysis of the stress-strain state, as well as the determination of the service life. The article is devoted to modeling of nonlinear creep of reinforced concrete structural elements taking into account damages and return of the creep. The high priority of the research topic is substantiated, the purpose and objectives are formulated. A combination of a plastic model with fracture mechanics is proposed to simulate the behavior of concrete in accordance with its characteristics, including not only stress and deformation, but also the degradation of its stiffness. The resulting equations of state correspond to the law reverse deformations. The finite element method is used to solve the boundary value problem. For the sake of numerical modeling of thin-walled structures, the use of special shell elements is proposed. The mathematical formulation of the problem of creep of reinforced concrete structural elements taking into account anisotropy of material properties and creep deformations and return of the creep is presented. Creep problems of thin-walled structural elements were solved with the help of developed software. Analyzed the deformation of reinforced concrete panel of cylinder. The analysis of the results allows us to judge the effectiveness of the proposed model as a whole. The equation of state reflects the anisotropy of the material properties and takes into account the damage, which allows for a reliable assessment of the strength, stiffness and durability of reinforced concrete structures. Conclusions about the adequacy of the analysis of reliability and durability of reinforced concrete structures using the proposed model.